2016
DOI: 10.1097/bsd.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Thoracic Spinal Stenosis-associated Myelopathy

Abstract: Onset of TSS was generally insidious but may be triggered acutely by apparently trivial events. Myelopathy mainly affected the lower limbs. The most common cause was OLF in the lower thoracic spine. Cervical or lumbar spinal disease was often also evident; therefore, comprehensive clinical assessment is required to avoid delays in diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 7 publications
1
78
0
Order By: Relevance
“…Thoracic ossification of the ligamentum flavum (TOLF) has been considered to be a leading cause of thoracic spinal stenosis and myelopathy [6]. One paper indicates that over 70% of patients suffering from thoracic spinal stenosis have been diagnosed with TOLF [7]. It has been suggested that some related factors are associated with TOLF, such as genetic factors, basic metabolic elements, and mechanical effects [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic ossification of the ligamentum flavum (TOLF) has been considered to be a leading cause of thoracic spinal stenosis and myelopathy [6]. One paper indicates that over 70% of patients suffering from thoracic spinal stenosis have been diagnosed with TOLF [7]. It has been suggested that some related factors are associated with TOLF, such as genetic factors, basic metabolic elements, and mechanical effects [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic ossification of the ligamentum flavum (OLF), which is the primary cause of thoracic spinal canal stenosis and myelopathy in our previous retrospective review, 1 is reported almost exclusively in East Asian countries 2 such as China, 3 Japan, 4 and Korea. 5 Our previous epidemiological survey revealed a standardized prevalence rate of 63.9% in Chinese people.…”
mentioning
confidence: 99%
“…Naturally, patients eventually admitted to our department when their symptoms are more serious for severe spinal cord compression. Patients with T-OLF always complain about trunk or lower extremities sensory abnormality, gait disturbance and urinary dysfunction [5].…”
Section: Introductionmentioning
confidence: 99%
“…Since the course of T-OLF is more insidious and slow, when the symptoms are obvious, it means that the spinal cord is severely compressed[16]. Patients with T-OLF may complained about muscle weakness, gait disturbance, numbness and sensory disturbance of the lower limb[5]. So surgical intervention is generally necessary for symptomatic OLF due to ineffective by using conservative treatment.…”
mentioning
confidence: 99%